2008
DOI: 10.1074/jbc.m803159200
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of Monomeric to Aggregated Forms of Aβ40 and Aβ42 Is an Important Determinant of Amyloid-β Aggregation, Fibrillogenesis, and Toxicity

Abstract: Aggregation and fibril formation of amyloid-␤ (A␤) peptides A␤40 and A␤42 are central events in the pathogenesis of Alzheimer disease. Previous studies have established the ratio of A␤40 to A␤42 as an important factor in determining the fibrillogenesis, toxicity, and pathological distribution of A␤. To better understand the molecular basis underlying the pathologic consequences associated with alterations in the ratio of A␤40 to A␤42, we probed the concentration-and ratio-dependent interactions between well de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
239
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(268 citation statements)
references
References 72 publications
24
239
2
3
Order By: Relevance
“…In agreement with Aβ42 having higher hydrophobicity and higher toxicity than Aβ40 in vitro and in vivo, a large number of reports also show that Aβ42 contributes to synaptic dysfunctions [31][32][33][34] . Herein, we compared the toxicity of Aβ40, Aβ42 and Aβ43.…”
Section: Neural Toxicity and Amyloid Pathology Of Aβ43mentioning
confidence: 64%
“…In agreement with Aβ42 having higher hydrophobicity and higher toxicity than Aβ40 in vitro and in vivo, a large number of reports also show that Aβ42 contributes to synaptic dysfunctions [31][32][33][34] . Herein, we compared the toxicity of Aβ40, Aβ42 and Aβ43.…”
Section: Neural Toxicity and Amyloid Pathology Of Aβ43mentioning
confidence: 64%
“…Traditionally, it was believed that Aβ1-42 is predominately responsible for toxicity observed in AD. Two key observations support this theory: 1) familial AD mutations in APP elevate the expression of Aβ1-42 [24,25]; and 2) Aβ1-42 is more prone to aggregation and is more toxic than Aβ1-40 [26,27]. However, it was reported that pyroglutamate-Aβ, which is also presented in AD plaques, could also be the toxic isoform of Aβ [28][29][30][31].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 92%
“…Whether some of these species represent off-or on-pathway intermediates to amyloid fibril formation remains unknown. Some of the key distinguishing features of protofibrillar aggregates are that they (i) contain a mixture of different secondary structure elements with a predominance of β-sheet 20 ; (ii) bind amyloid-specific dyes, such as Congo red and Thioflavin-T (ThT), although less strongly than mature fibrils [20][21][22] ; and (iii) are less stable than mature amyloid fibrils and exist in equilibrium with monomeric Aβ 20,21,23 . In the presence of monomeric Aβ, all these species convert to mature amyloid fibrils by monomer addition.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of lyophilized Aβ with strong acids and bases to disrupt preformed aggregates and enhance solubility 52 , filtration through LMW cutoff filters 53 , photo-induced crosslinking of unmodified proteins 17 , density gradient centrifugation 54 and size exclusion chromatography (SEC) 13,14,17 have all been used to prepare soluble aggregates of Aβ and yield preparations that vary in size and morphology distribution. SEC, in particular, offers several advantages: (i) a variety of column matrices with different separation capacities are readily available and can be used in isolation or in combination with other columns to obtain high-resolution separation and fractions containing Aβ aggregates of defined size distribution; (ii) generally, the columns are equipped with filters at the top that allow for the removal of fibrillar (or insoluble) material from the injected sample, thus ensuring that the Aβ fractions are free of fibrillar seeds; (iii) if SEC is coupled to a light-scattering detector, accurate determination of Aβ aggregates' size distribution becomes possible 20 ; (iv) in analytical mode, SEC is a valuable tool to monitor early events in amyloid formation and quantification of monomer and/or protofibril loss during the time course of fibril formation 21 ; and (v) by choosing proper running conditions (i.e., buffer pH and contents), fractions are obtained in solution conditions suitable for biological systems, free of harmful or undesired substances (e.g., organic solvents and so on). SEC has also been successfully used to isolate Aβ oligomers (such as dimers and trimers) and high-molecular-weight aggregates (including protofibrils and amorphous aggregates) from complex cell culture media 55 or from postmortem AD brain extracts 56 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation